2005
DOI: 10.1111/j.1365-2095.2005.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of ingredients included in shrimp feeds to stimulate intake

Abstract: The inclusion in feed formulations of ingredients that act as attractants and feeding incitants or stimulants has been proposed as a means of increasing feed consumption, and hence growth, of farmed shrimp. Squid, crustacean and krill meals, fish and krill hydrolysates and a betaine product (Finnstim) were examined to assess their relative effectiveness in increasing the feed intake of black tiger shrimp Penaeus monodon. These presumed feeding effectors were added to a base feed at between 5 and 50 g kg−1. Giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 10 publications
6
76
1
5
Order By: Relevance
“…Although crayfish have polytrophic feeding habits (Saoud & Ghanawi 2013) Fenucci et al 1980, Díaz et al 1999, Smith et al 2005, Nunes et al 2006) even though the SM and the method for incorporating it into the experimental feed were the same across all studies. However, these other studies were performed on marine crustaceans (lobsters and shrimp), whereas this study is the first to test the effectiveness of SM as an attractant for a freshwater decapod.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although crayfish have polytrophic feeding habits (Saoud & Ghanawi 2013) Fenucci et al 1980, Díaz et al 1999, Smith et al 2005, Nunes et al 2006) even though the SM and the method for incorporating it into the experimental feed were the same across all studies. However, these other studies were performed on marine crustaceans (lobsters and shrimp), whereas this study is the first to test the effectiveness of SM as an attractant for a freshwater decapod.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that squid meal acts as a stimulant, increasing food consumption in Homarus gammarus (Mackie & Shelton 1972), Penaeus stylirostris and P. setiferus (Fenucci et al 1980), P. monodon (Smith et al 2005), and Litopenaeus vannamei (Nunes et al 2006). Similarly, shrimp protein hydrolysates stimulate feed consumption in C. quadricarinatus (Arredondo-Figueroa et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…; n = 7) at two inclusion levels (0.5% or 1.0%) compared with a control ingredient (neutral gelatin + 3% soybean meal) chemicals, such as amino acids, mainly taurine, glycine, arginine, glutamic acid and alanine; small peptides, amines, nucleotides and nucleosides, and quaternary ammonium bases, such as betaine (Lee and Meyers, 1997). Protein-rich ingredients of marine origin, such as fishmeal and squid meal contain these substances which are feeding effectors for shrimp (Smith et al, 2005). Hence, the present results for FMPO and FMBO were expected and confirm the superior ability of marine fishmeal to stimulate L. vannamei chemoreceptors.…”
Section: Validation Phasementioning
confidence: 99%
“…Smith et al (2005) examined squid, crustacean and krill meals, fish and krill hydrolysates and a betaine product as stimulants in black tiger shrimp Penaeus monodon diets. These authors concluded that P. monodon showed a significantly greater preference for feeds containing crustacean or krill meal.…”
Section: Introductionmentioning
confidence: 99%
“…Because extrinsic factors can be manipulated, current aquaculture research has focused on managerial aspects such as encouraging the feed consumption by incorporation of feed attractants which in turn improve the survival and shorten the production intervals. The feed attractants are specific compounds or ingredients added to the feed to enhance the diet palatability and consequently, its acceptability by fish (Smith, Tabrett, Barclay, & Irvin, 2005). As a result of the improvement in the diet acceptability, the fish can adapt earlier to artificial dry diet during the weaning period and attain a higher overall feed consumption and growth rate (Tandler, Berg, & Mackie, 1982;Kolkovski, Arieli, & Tandler, 1997;de Oliveira & Cyrino, 2004;Gaber, 2005).…”
Section: Introductionmentioning
confidence: 99%